2004
DOI: 10.1529/biophysj.104.040105
|View full text |Cite
|
Sign up to set email alerts
|

Structural Calorimetry of Main Transition of Supported DMPC Bilayers by Temperature-Controlled AFM

Abstract: Atomic force microscopy at high temperature resolution (DeltaT < or approximately 0.1 K) provided a quantitative structural calorimetry of the transition from the fluid (Lalpha)- to the gel (Pbeta')-phase of supported dimyristoylphosphatidylcholine bilayers. Besides a determination of the main transition temperature (T0) and the van't Hoff transition enthalpy (DeltaHvH), the structural analysis in the nm-scale at T close to T0 of the ripple phase allowed an experimental estimation of the area of cooperative un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 66 publications
(104 reference statements)
15
83
0
Order By: Relevance
“…The formation of the ripple-gel-phase P b' as a pre-melting transition [12,13] was not detected in the experiments. The large image sizes and the surface roughness of the glass substrate impede the visualization of ripple phases, but we have experimental evidence from lipid patch analysis on mica at higher magnification, to show that the P b' phase occurs during the melting process (results not shown) in accordance with the results of Kolb and coworkers.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…The formation of the ripple-gel-phase P b' as a pre-melting transition [12,13] was not detected in the experiments. The large image sizes and the surface roughness of the glass substrate impede the visualization of ripple phases, but we have experimental evidence from lipid patch analysis on mica at higher magnification, to show that the P b' phase occurs during the melting process (results not shown) in accordance with the results of Kolb and coworkers.…”
mentioning
confidence: 74%
“…Characteristic lipid patches, visible on the left hand side of the bilayer stripe, help to locate the image and its magnification, allowing images of the same size and position to be produced At low temperature (15.6 8C) an average bilayer thickness d ave , of 4.70 AE 0.02 nm was found which is in good agreement with the study from Kolb and coworkers who found a bilayer thickness of 4.8 nm in the gel phase also employing AFM. [12] Upon heating, the structured bilayer maintains its initial surface coverage of 0.59 AE 0.03 and average thickness of 4.7 AE 0.02 nm up to 26.4 8C. However, the AFM image at 26.4 8C shows weak structural changes of the microstructured bilayer (arrow).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The main transition temperature, T m , at atmospheric pressure is 296 K for a pure DMPC bilayer, 83 while it is around 311 K for a pure DMTAP bilayer. 84 For DMPC/DMTAP mixtures, T m depends on the molar fraction of DMTAP, TAP ; experiments at 3 bar 85 have shown that T m ( TAP ) is downward concave and has a global maximum of 310 K at around TAP ∼ 45 mol %.…”
Section: Simulation Details and Setupmentioning
confidence: 99%